IMPACT OF FRIENDSHIP CIRCLE ON UNIVERSITY STUDENTS’ PERCEPTION, ATTITUDE, BEHAVIOR AND ACADEMIC PERFORMANCE - Zartashia Kynat Javaid; Fareeha Kabeer; Abida Kareem (Policy Research Journal, 2025)
This qualitative study investigates the impact of friendship circles on university students’ behavior, attitude, perception, and academic success. Semi-structured interviews were conducted from 10 young university students’, divided evenly between first and final year students. Convenient sampling technique was used, and the data was analyzed thematic analysis.. The findings reveal complex dynamics, with friendship groups exerting both positive and negative influences on students’ academic performance, mental health, and personal growth. The study highlights the need for universities to provide support services addressing emotional and academic needs. It is recommended to educators, policymakers, and mental health professionals to acknowledge the effects of friendship circles on students’ well-being. The study emphasizes the importance of friendship circles in influencing university students’ experiences and outcomes.